3D printing of cell-delivery scaffolds for tissue regeneration. (27th March 2023) - Xue, Jianmin; Qin, Chen; Wu, Chengtie
Abstract: Tissue engineering strategy that combine biomaterials with living cells has shown special advantages in tissue regeneration and promoted the development of regenerative medicine. In particular, the rising of 3D printing technology further enriched the structural design and composition of tissue engineering scaffolds, which also provided convenience for cell loading and cell delivery of living cells. In this review, two types of cell-delivery scaffolds for tissue regeneration, including 3D printed scaffolds with subsequent cell-seeding and 3D cells bioprinted scaffolds, are mainly reviewed. We devote a major part to present and discuss the recent advances of two 3D printed cell-delivery scaffolds in regeneration of various tissues, involving bone, cartilage, skin tissues etc. Although two types of 3D printed cell-delivery scaffolds have some shortcomings, they do have generally facilitated the exploration of tissue engineering scaffolds in multiple tissue regeneration. It is expected that 3D printed cell-delivery scaffolds will be further explored in function mechanism of seeding cells in vivo, precise mimicking of complex tissues and even organ reconstruction under the cooperation of multiple fields in future. Graphical abstract: